Fire Resistance Investigation of Simple Supported RC Beams with Varying Reinforcement Configurations - Yamin Song; Chuanguo Fu; Shuting Liang; Ankang Yin; Longji Dang (Advances in Civil Engineering)
To investigate fire-resistance behaviors of simple supported reinforced concrete (RC) beams with three faces exposed to fire, six full-scale specimens were designed in accordance with the principle of “strong bending and weak shearing.” One beam was treated as the control case of room temperature while the other five beams were exposed to high temperature. Parameters related to shear capacity were discussed, such as longitudinal reinforcement ratio and stirrup ratio. The experimental results show that brittle shear failure under room temperature may transfer to shear-bend failure at high temperature due to thermal expansion and strength degradation of concrete and steel. The greater the longitudinal reinforcement ratio, the longer the failure time of specimens. It indicates that the pinning action of longitudinal reinforcement can significantly improve the shear capacity of beams under high temperature. In addition, the configuration of stirrup reinforcement can effectively reduce the brittle change of vertical deflection when the beam enters the failure stage.